2004
DOI: 10.1212/01.wnl.0000129913.44351.a3
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of the vascular endothelial growth factor in CSF from early ALS patients

Abstract: Deletion of the hypoxia-response element in the vascular endothelial growth factor (VEGF) promoter causes motor neuron degeneration in a mouse model. "At-risk" haplotypes with low circulating VEGF levels have been demonstrated in humans. Here the authors report low VEGF levels in the CSF of ALS patients during their first year of the disease, independently of VEGF promoter polymorphism. This finding early in ALS patients suggests a possible role for VEGF gene regulation in the pathogenesis of ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
3
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 9 publications
5
61
3
2
Order By: Relevance
“…38,[41][42][43] Of these neurotrophic factors, VEGF is well known to have an important function in the pathogenesis of ALS. [31][32][33][34]37,38 The genetically modified human NSCs we established, F3.VEGF cells, were confirmed to release four times of VEGF165, the most abundant and biologically active isoform in vivo, compared with the parental F3 cells as we have reported previously in animal models of stroke. 28 Ex vivo gene therapy by genetically modified cells to carry growth factor gene has no risk related with virus injection during the in vivo gene therapy, and the transplanted cells can deliver growth factor over a large area as the cells migrate and are integrated to the host brain tissue.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…38,[41][42][43] Of these neurotrophic factors, VEGF is well known to have an important function in the pathogenesis of ALS. [31][32][33][34]37,38 The genetically modified human NSCs we established, F3.VEGF cells, were confirmed to release four times of VEGF165, the most abundant and biologically active isoform in vivo, compared with the parental F3 cells as we have reported previously in animal models of stroke. 28 Ex vivo gene therapy by genetically modified cells to carry growth factor gene has no risk related with virus injection during the in vivo gene therapy, and the transplanted cells can deliver growth factor over a large area as the cells migrate and are integrated to the host brain tissue.…”
Section: Discussionsupporting
confidence: 59%
“…31 Subsequent follow-up human genetic studies have shown that 'low-VEGF' haplotypes in the VEGF promoter had an increased risk of ALS in the European population. 38 Several reports have also reported low VEGF levels in the colony-stimulating factor of ALS patients, [32][33][34] and the expression of both VEGF and VEGFR2 was downregulated on the anterior horn motoneurons as compared with the normal controls. 39 These studies have prompted us to use VEGF as a candidate trophic factor for treatment of the transgenic mouse model of ALS in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most recently, Azzouz and colleagues (2004) found that intramuscular injection of a VEGF-expressing lentiviral vector delayed onset and slowed progression of ALS in mice. In addition, a recent study found low VEGF levels in the cerebrospinal fluid of patients with early stages of ALS (Devos et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…A decrease in endogenous production of VEGF has been linked to motor neuron degeneration in motor system diseases such as amyotrophic lateral sclerosis (ALS) and Kennedy disease [2,7,10,14,23,24,31]. Also, impairing VEGF production through genetic manipulation results in degeneration of lower motor neurons in adulthood [14,23].…”
Section: Introductionmentioning
confidence: 99%